Injury Causes and Recovery Management Strategies among Singapore CrossFitters - Tan, Kun Lan; Chung, Ho Jin (ACPES Journal of Physical Education, Sport, and Health (AJPESH), 2021)
CrossFit is a combination of movements from various sport disciplines such as Olympic Weightlifting, Powerlifting and Gymnastics executed at high intensity. It has shown to bring about physiological and psycho-social benefits to members, increasing exercise adherence. Established in 2005, CrossFit has seen an exponential growth since, with 13,991 CrossFit affiliates worldwide. The popularity of the program despite its disposition to injury requires greater attention to its safety. This research aims to understand (1) reasons of injury among CrossFitters; (2) Injury management techniques among CrossFitters. In-depth interviews were conducted with nine CrossFitters from five Singapore CrossFit affiliates. Data was transcribed and thematically analyzed. Findings revealed that causes of injury include poor workout program designs, insufficient physiological knowledge passed down from coaches to athletes, athlete’s impatience when learning new skills as well as athletes conforming to performance and peer pressures. Further, Crossfitters manage their injuries through self-care physiological means and with professional guidance. The study concludes that coaches play a vital role in both the prevention and management of injuries. Therefore, they should design their programs with the athlete’s safety in mind and foster an environment that values patience, strength building discipline and safety. Athletes should also pay extra attention to their movement technique and be self-reflective in their physical capabilities. All athletes should regularly practice conservative physiological recovery methods and seek treatment or diagnosis from medical practitioners when necessary.